Efektivitas Kenaikan Tarif Pajak Bumi dan Bangunan pada Badan Pendapatan Daerah Kabupaten Biak Numfor - Djunaedi Djunaedi; Amiruddin Amiruddin; Marlyn Leonita Sroyer (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effectiveness of the policy to increase Land and Building Tax (PBB) rates at the Regional Revenue Agency of Biak Numfor District and to identify the factors that influence it. The policy to increase PBB rates is implemented based on Government Regulation Number 35 of 2023, with the hope of increasing Local Own Revenue (PAD). However, its implementation in the field has not shown optimal results. This research uses a descriptive qualitative approach, with data collection through in-depth interviews, observations, and documentation studies.The results of the study indicate that the effectiveness of the policy to increase PBB rates is still low. Tax revenue achievements have not met the targets set by the local government. Several factors influencing the effectiveness of this policy include the low taxpayer compliance, weak tax administration system, lack of socialization and education for the public, and the perception of unfairness in tariff determination. This finding is reinforced by interviews with officials from Bapenda, which revealed implementation challenges from both technical and social perspectives. This study uses the theory of Devi & Mangoting (2020) as an analytical framework, emphasizing that tax effectiveness is influenced by the administration system, compliance, and public understanding. The results of this study imply that the success of fiscal policies is not solely determined by regulations, but is also significantly affected by social and institutional aspects. Recommendations include enhancing the digitalization of the tax system, expanding education, and adjusting tariffs based on the economic conditions of the community.